EKSISTENSI PENDIDIKAN ISLAM DALAM UPAYA PENURUNAN TINGKAT KRIMINALITAS PADA DAERAH RAWAN KRIMINAL DI LAMPUNG TIMUR - Hasanah, Uswatun; Masitoh, Dewi; Khasanah, Uswatun; Akmansyah, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2021)
East Lampung as one of the crime-prone areas has shown a very rapid decline in crime rates in the last three years, followed by an increase in community enthusiasm and participation in Islamic education. This study aims to determine the extent of Islamic education in reducing crime rates in crime-prone areas in East Lampung. The research method used is descriptive qualitative with a case study approach by selecting the four most crime-prone areas in East Lampung. The sources of data of this research are several religious counselors, local religious leaders, and the surrounding community by selecting samples by purposively using the interview as the main instrument, observation and documentation as secondary intrument. The results of the study found out that East Lampung experienced a drastic reduction in the crime rate due to the development of Islamic informal education, namely Majlis Taklim, Qur’anic schools, Madrasah Diniyah and Islamic Boarding Schools that encourage the drastic changes in attitudes and behavior to be more religious and better. Besides, that able to strengthen community relations and can be a medium for various conflict resolutions between residents so that crime rates can be optimally reduced and the quality of social life in the community can be continually optimized.